Kinetics of T‐cell subset reconstitution following treatment with bendamustine and rituximab for low‐grade lymphoproliferative disease: a population‐based analysis. (13th December 2018) - Martínez‐Calle, Nicolás; Hartley, Sarah; Ahearne, Matthew; Kasenda, Benjamin; Beech, Amy; Knight, Helen; Balotis, Constantine; Kennedy, Ben; Wagner, Simon; Dyer, Martin J. S.; Smith, Dean; McMillan, Andrew K.; et al.
Summary: Delayed lymphocyte and T‐cell immune reconstitution following bendamustine‐rituximab (BR) for indolent non‐Hodgkin lymphoma (iNHL) has been described, but no information is available for chronic lymphocytic leukaemia (CLL). We present a population‐based retrospective analysis of immune reconstitution and risk of infection following BR. Outcomes included timing/correlates of CD4+ recovery and risk of ≥grade 3 infections. Consecutively treated patients (1 April 2014 to 31 January 2017) were included ( n = 295), with a median age of 65 years (range 33–92); 57% were 1st line treatments. Median cumulative bendamustine dose was 1080 mg/m 2 (range 140–1440 mg/m 2 ). CD4/CD8/CD19/NK subsets were available for 148 patients. Median follow‐up was 24 months. Median times to lymphocyte count (ALC) recovery (≥1 × 10 9 /l) and CD4+ recovery (≥0·2 × 10 9 /l) were 26 and 24 months, respectively. Bendamustine total dose >1080 mg/m 2 (hazard ratio [HR] 0·4; 95% confidence interval [CI]: 0·2–0·8), end‐of‐treatment ALC ≤0·4 × 10 9 /l (HR 0·53; 95% CI: 0·3–0·9) and CD4+ <0·1 × 10 9 /l 1‐year post‐BR (HR 0·03; 95% CI: 0·008–0·15) were covariables for delayed CD4+ recovery. ALC‐recovery ≥1 × 10 9 /l was an unreliable predictor of CD4+ recovery (negative predictive vale 74%, positive predictive value 86%, likelihood ratio 3·3). CD4+ lymphopenia >3 years was a significant risk factor for ≥grade 3 infections (Odds ratio 3·4; 95% CI: 1·4–6·9). CD4+ recovery after BR is unexpectedly delayed and late recovery is associated with risk of serious infections. Monitoring CD4+ following BR could identify patients at high risk of delayed infections.